DRD2/ANKK1 Polymorphism Modulates the Effect of Ventral Striatal Activation on Working Memory Performance - Nymberg, Charlotte (Nature Publishing Group, 2014)
Motivation is important for learning and cognition. Although dopaminergic (D2) transmission in the ventral striatum (VS) is associated with motivation, learning, and cognition are more strongly associated with function of the dorsal striatum, including activation in the caudate nucleus. A recent study found an interaction between intrinsic motivation and the DRD2/ANKK1 polymorphism (rs1800497), suggesting that A-carriers of rs1800497 are significantly more sensitive to motivation in order to improve during working memory (WM) training. Using data from the two large-scale imaging genetic data sets, IMAGEN (n=1080, age 13–15 years) and BrainChild (n∼300, age 6–27), we investigated whether rs1800497 is associated with WM. In the IMAGEN data set, we tested whether VS/caudate activation during reward anticipation was associated with WM performance and whether rs1800497 and VS/caudate activation interact to affect WM performance. We found that rs1800497 was associated with WM performance in IMAGEN and BrainChild. Higher VS and caudate activation during reward processing were significantly associated with higher WM performance (p<0.0001). An interaction was found between the DRD2/ANKK1 polymorphism rs1800497 and VS activation during reward anticipation on WM (p<0.01), such that carriers of the minor allele (A) showed a significant correlation between VS activation and WM, whereas the GG-homozygotes did not, suggesting that the effect of VS BOLD on WM is modified by inter-individual genetic differences related to D2 dopaminergic transmission.